Respuesta :

Hope you understand it!
Ver imagen trishathapa

Given that:

[tex]a=2, b=-2[/tex]

Substituting these values,

[tex]2a^{2} b+2ab^{2} +ab[/tex]

[tex] = > 2 \times ({2} \times 2) \times ( - 2) + 2 \times 2 \times ( - 2 \times - 2) + (2 \times - 2)[/tex]

[tex] = > 2 \times 4 \times ( - 2) + 4 \times 4 + ( - 4)[/tex]

[tex] = > 8 \times ( - 2) + 16 + ( - 4)[/tex]

[tex] = > - 16 + 16 + (- 4)[/tex]

As first two 16's will be cancelled as they have opposite signs, so, the remaining is,

[tex] - 4[/tex]

ACCESS MORE